Nanostructure and stoichiometry tailoring of CoS2 for high performance hydrogen evolution reaction. (19th May 2023) - Hu, Yingfei; Qi, Yujia; Pi, Mingyu; Qiao, Yi; Hao, Lingyun; Wang, Yuanyuan; Guan, Hangmin; Feng, Jianyong
Abstract: Developing efficient and low-cost electrocatalysts for hydrogen evolution reaction (HER) is important for hydrogen fuel production. In this study, we synthesized two different types of CoS2 under low sulfur (LS) and high sulfur concentration (HS) conditions. Structural analysis results show that CoS impurity phase forms easily when the concentration of sulfur is low, while at high sulfur concentration the growth of CoS impurity phase is inhibited and leads to phase-pure CoS2 . Electrochemical investigation of HER performance reveals that the onset potential of CoS2 (HS) electrode (ca. − 0.11 V vs. the reversible hydrogen electrode, RHE) is 30 mV anodic of the CoS2 (LS) one (ca. − 0.14 V vs. RHE). At a specific current density of 10 mA cm −2 the required overpotential on CoS2 (HS) electrode is only 163 mV, which is 40 mV less than the CoS2 (LS) electrode. Electrochemical impedance spectroscopy (EIS) data further demonstrate that the charge transfer rate of CoS2 (HS) electrode is faster than that of CoS2 (LS) electrode towards HER. Highlights: CoS2 electrocatalysts with two different nanostructures and stoichiometries are produced. Sulfur concentration plays a key role in the synthesis of CoS2 . High sulfur concentration is conducive to reducing the formation of sulfur vacancies.